TRADISI BASIACUONG DESA KOTO TIBUN KECAMATAN KAMPAR KABUPATEN KAMPAR - Nover Yarna; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study examines the Tradition of Basiacuong Koto Tibun Kecamatan Kampar Kabupaten Kampar. Basiacuong is one of the language culture of Kampar custom in general, is also a custom of the people of Desa Koto Tibun. This custom is inherited from their ancestors. Basiacuong used by ninik mamak Kampar in various custom events or not, such as opening Undiong